Spectrophotometric pH measurements from continuous surface water supply and discrete samples - Jens Daniel Müller; Gregor Rehder (PANGAEA, 2021)
The BONUS INTEGRAL field expeditions on RV Aranda took place from February 28th 2019 to March 11th 2019 (RV Aranda Cruise 04/19). The scientific program of was tailored to serve the purposes of BONUS INTEGRAL. This dataset provides surface data for the creation of maps of surface concentrations of pH via continuous surface water measurements and discrete samples. Spectrophotometric determination of pH by using CONTROS HydroFIA pH system. The HydroFIA pH system (4H Jena Engineering, 24148 Kiel, Germany) is a continous sample flow instrument for determination of the pH value. In the dependence of the sample pH value the injekted indicator m-cresol purple (supplier of the instrument) change the coulor and from the resulting absorption ranges (ratio) the pH can be calculated. The measuring principle and calculation is based on Dickson et al. [2007] and Müller and Rehder [2018]. For the pH measurement of discrete samples 250 ml ground-glass bottles were used. These bottles are measured directly after sampling. A 5-fold measurement is performed from the same bottle. The last 3 measurements are used for averaging. According to the manufacturer an accuracy of 0.005 is guaranteed and a precision of 0.002 is possible. For control measurements, in-house buffer solutions are used, which are measured at regular intervals.